Precipitation drives global variation in natural selection - Siepielski, A.; Morrissey, M.; Buoro, M.; Carlson, S.; Caruso, C.; Clegg, S.; Coulson, T.; Di Battista, Joseph; Gotanda, K.; Francis, C.; Hereford, J.; Kingsolver, J.; et al. (The American Association for the Advancement of Science, 2017)
Climate change has the potential to affect the ecology and evolution of every species on Earth. Although the ecological consequences of climate change are increasingly well documented, the effects of climate on the key evolutionary process driving adaptation-natural selection-are largely unknown. We report that aspects of precipitation and potential evapotranspiration, along with the North Atlantic Oscillation, predicted variation in selection across plant and animal populations throughout many terrestrial biomes, whereas temperature explained little variation. By showing that selection was influenced by climate variation, our results indicate that climate change may cause widespread alterations in selection regimes, potentially shifting evolutionary trajectories at a global scale.